2019
DOI: 10.1111/scs.12644
|View full text |Cite
|
Sign up to set email alerts
|

Training professionals in a recovery‐oriented methodology: a mixed method evaluation

Abstract: Background Several studies have reported difficulties concerning the implementation of recovery‐oriented interventions. In this study, the effect of training in the Comprehensive Approach to Rehabilitation (CARe) on daily practice was evaluated. Additionally, we aimed to acquire insight into the experiences with the implementation process involving professionals, management and trainers. Methods Fourteen teams for sheltered and supported housing in the Netherlands participated in this study. As part of a clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…In addition, while some studies have neglected to report the psychometric findings of their instruments (18,22,23), others have reported only Cronbach's α scores for the four subscales, without examining the factor structure (15,17,24). Hence, reported results regarding the four presumed dimensions may be unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, while some studies have neglected to report the psychometric findings of their instruments (18,22,23), others have reported only Cronbach's α scores for the four subscales, without examining the factor structure (15,17,24). Hence, reported results regarding the four presumed dimensions may be unreliable.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treatment may focus on equipping patients with the abilities necessary to overcome the deficits they perceive, for example by offering tips for managing their finances. Alternatively, treatment may focus on helping patients find new goals that are more in line with their opportunities [50]. Overall, the results of this study imply that treatment of people with severe mental health problems should include all facets of life in its attempt to improve the QoL of patients.…”
Section: Discussionmentioning
confidence: 82%
“…Previous research has found such training successful. The effect levelled out somewhat over time [34], indicating that such training should be part of continuous staff education. A third alternative could be to apply the principle of place-then-train, used in work rehabilitation according to the Individual Placement and Support model [35].…”
Section: Implications For Support For Activity In the Sh Contextmentioning
confidence: 99%